ALI BORONI-МИ ЁКИ ALBERINIUS ? НЮАНС: АЛ-БЕРУНИЙ АСАРЛАРИНИНГ ЕВРОПАДАГИ ДАСТЛАБКИ ТАРЖИМАЛАРИГА ОИД АЙРИМ МУЛОҲАЗАЛАР (Scientific journal of the Fergana State University, 2023)
In the article on the basis of careful analysis of the scientific literature devoted to history of the translations in Europe in XI–XIII centuries, essential amendments purpose of which is elimination of some mistakes and absurdities in the European translations of the works by al-Beruni.